Efficacy of transvaginal cervical cerclage in women at risk of preterm birth following previous emergency cesarean section. (2nd September 2020) - Hickland, Maria M.; Story, Lisa; Glazewska‐Hallin, Agnieszka; Suff, Natalie; Cauldwell, Matthew; Watson, Helena A.; Carter, Jenny; Duhig, Kate E.; Shennan, Andrew H.
Abstract: Introduction: Emergency cesarean sections (EMCS) are associated with subsequent preterm birth, particularly at full dilation (FDCS), which is a cause of both second trimester miscarriages and early, recurrent spontaneous preterm birth (sPTB). The optimal management for these women in subsequent pregnancies is currently unknown. This study aims to assess efficacy of transvaginal cervical cerclage (TVC) in prevention of preterm birth among women who have had an EMCS followed by a subsequent late miscarriage or sPTB. Material and methods: A historical cohort study was performed assessing outcomes of women attending the Preterm Surveillance Clinic at St Thomas' Hospital, London, who received TVC, with a history of EMCS (pregnancy A) followed by a sPTB/late miscarriage (pregnancy B) and a subsequent pregnancy (pregnancy C). A historical reference group managed in the same clinic was identified comprising women with any risk factor for sPTB, who required TVC. Incidence of delivery >24 to <30 weeks' gestation was compared with relative risk and 95% confidence intervals (CI). Subgroup analysis was carried out assessing women who had a previous FDCS. Results: 209 women with a previous EMCS during labor (50 with FDCS), followed by sPTB/late miscarriage were identified. 178 progressed beyond 24 weeks; of these, 56 received TVC and formed the study group. 905 high‐risk women were identified; of these, 154 received TVC and formed the reference group. Despite TVC treatment, 17/56 (30%) of the study group delivered <30 weeks' gestation compared with 5/154 (3%) of the reference group (RR 9.4, 95% CI 3.6‐24.2, P < .001). In the subset of 17 women in the study group with a previous FDCS, followed by sPTB/late miscarriage, 6/17 (35%) delivered <30 weeks' gestation, significantly higher than the reference group ( P < .001) but similar to EMCS at less than full dilation (35% vs 28%, P = .596). Overall, 33/72 (46%) women receiving cerclage with prior EMCS had either a mid‐trimester loss or delivery <30 weeks. Conclusions: Transvaginal cervical cerclage appears less effective in preventing preterm birth among pregnant women who have had an EMCS followed by a sPTB/late miscarriage compared with other high‐risk women. The lack of efficacy in the subgroup with an FDCS was similar.